Characterization of the Poplar R2R3-MYB Gene Family and Over-Expression of PsnMYB108 Confers Salt Tolerance in Transgenic Tobacco - Zhao, Kai; Cheng, Zihan; Guo, Qing; Yao, Wenjing; Liu, Huajing; Zhou, Boru; Jiang, Tingbo (Frontiers in Plant Science, 2020)
The MYB, one of the largest transcription factor families in plants, is related to various biological processes. For an example, the R2R3-MYB family plays an important role in regulation of primary and secondary metabolism, plant growth and development, and responses to hormones and stresses. However, functional studies on the poplar R2R3-MYB genes are limited. In this study, we identified 207 poplar R2R3-MYB genes that are unevenly distributed on the 19 chromosomes of poplar, followed by characterization of their conserved domains. On the basis of phylogenetic analysis, these genes can be divided into 23 groups. Evidence from synteny analyses indicated that the poplar R2R3-MYB gene family is featured by tandem and segmental duplication events. On the basis of RNA-Seq data, we investigated salt responsive genes and explored their expression patterns. Furthermore, we cloned the PsnMYB108 gene from poplar, which is significantly up-regulated in roots and leaves in response to salt stress. To validate its function, we developed transgenic tobacco plants that over-express the PsnMYB108 gene. It appears that the transgenic lines are more tolerant to salt stress than the wild type does. Evidence from physiological analyses demonstrated that over-expression of PsnMYB108 may improve tobacco salt stress tolerance by increasing the reactive oxygen species scavenging ability and the accumulation of proline. These results laid the foundation for future analysis and functional studies of poplar R2R3-MYB family members, and revealed that PsnMYB108 plays an important role in improving plant salt stress tolerance.